2015
DOI: 10.4209/aaqr.2015.04.0258
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption Trends and Decoupling Effects between Carbon Dioxide and Gross Domestic Product in South Africa

Abstract: This study evaluates the occurrence of decoupling of CO 2 emissions from Gross Domestic Product (GDP) in South Africa (SA) for the period of 1990 to 2012 by using the Organization for Economic Cooperation and Development (OECD) and Tapio methods, and identifies the primary CO 2 emissions driving forces by the Kaya identity. The results showed a strong decoupling during the period of 2010-2012, which is considered as the best development situation. In 1994-2010 SA had a weak decoupling; while during the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Additionally, the economic effect was the main factor leading to increased CO 2 emissions from Thailand's thermal power generation, whereas electricity intensity played a major role in decreasing CO 2 emissions. Liou et al (2015) Lin et al (2015) evaluated the decoupling of CO 2 emissions from GDP in South Africa using OECD and Tapio during the period 1990-2012, and they investigated the primary CO 2 emission drivers with the Kaya identity. Results showed that a strong decoupling occurred during 2010-2012, and the increase in population, GDP per capita, and adverse energy efficiency were the primary driving forces for increased CO 2 emission.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the economic effect was the main factor leading to increased CO 2 emissions from Thailand's thermal power generation, whereas electricity intensity played a major role in decreasing CO 2 emissions. Liou et al (2015) Lin et al (2015) evaluated the decoupling of CO 2 emissions from GDP in South Africa using OECD and Tapio during the period 1990-2012, and they investigated the primary CO 2 emission drivers with the Kaya identity. Results showed that a strong decoupling occurred during 2010-2012, and the increase in population, GDP per capita, and adverse energy efficiency were the primary driving forces for increased CO 2 emission.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lin et al (2015) used the Organization for Economic Cooperation and Development (OECD) and Tapio methods to analyze the relationship between CO 2 emissions and the Gross Domestic Product (GDP) of South Africa for the period of 1990 to 2012. Dimoula et al (2016) used the conversion factor of 3.06 kg CO 2 per diesel liter in a freight road transport system.…”
Section: Resultsmentioning
confidence: 99%
“…Existing evaluations examine single instruments such as environmental fiscal reform [9] and emissions trading schemes, or policy mixes comprised of several instruments [10,11]. Policy analyses often focus on progress towards specific objectives such as reducing energy consumption [12], municipal waste [13], carbon emissions [14,15] and fresh water use [16,17].…”
Section: Existing Research In the Field Of Decouplingmentioning
confidence: 99%
“…Policy analyses often focus on progress towards specific objectives such as reducing energy consumption [12], municipal waste [13], carbon emissions [14,15] and fresh water use [16,17]. The scale of decoupling analyses varies, some focusing on a sector [18,19], while others look at city [20], regional/provincial [21] and national [11,[13][14][15]22] levels, including cross comparisons [12,23,24].…”
Section: Existing Research In the Field Of Decouplingmentioning
confidence: 99%